Contrast-enhanced ultrasound (CEUS) for the diagnosis of axillary lymph nodes in breast cancer: A systematic review and meta-analysis - Le Chong; Luhua Xia; Xiulan Wu; Hongyu Li; Zhiying Jia (WFUMB Ultrasound Open)
Objective: To evaluate the accuracy of contrast-enhanced ultrasound (CEUS) for the diagnosis of axillary lymph nodes in breast cancer. Methods: PubMed, EMBASE, The Cochrane Library, Chinese Biomedical Literature Database, the full database of China, Chinese National Knowledge Infrastructure, and Wanfang database databases were utilized. Perspective studies regarding CEUS diagnosis of axillary lymph nodes in breast cancer were included. QUADAS-2 was used to estimate the research quality by two reviewers independently. Metadisc1.4 software and Stata 14.0 were used to examine data from the included studies. The diagnostic value of CEUS was assessed by aspects such as summary sensitivity, specificity, receiver operating characteristic (SROC). Results: Fourteen studies were included and 1127 patients were included. A meta-analysis showed that the summary sensitivity of CEUS was 0.85 (95 % CI 0.82–0.87), the specificity was 0.86 (95 % CI 0.82–0.89), the diagnostic odds ratio was 31.15 (95 % CI 17.16–56.52) and the SROC was 0.9186. Conclusions: CEUS diagnosis of axillary lymph nodes in breast cancer has high sensitivity and specificity and it is the preferred method to diagnose axillary lymph nodes in breast cancer in clinical practice.